2009
DOI: 10.1111/j.1365-2133.2009.09077.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective vs. subjective factors in the psychological impact of vitiligo: the experience from a French referral centre

Abstract: Subjective as well as objective factors should be included in the assessment of disease severity and follow-up of patients with vitiligo. A simple perceived severity scale is useful in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
4
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 33 publications
10
77
4
7
Order By: Relevance
“…It is believed that higher DLQI scores are associated with darker skin as the contrast with skin color in dark-skinned people attracts more unwanted attention, which is emotionally disturbing and upsetting [23,28,29,37]. Cultural and religious differences may also be taken into account to explain such discrepancies [9,20,22,28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that higher DLQI scores are associated with darker skin as the contrast with skin color in dark-skinned people attracts more unwanted attention, which is emotionally disturbing and upsetting [23,28,29,37]. Cultural and religious differences may also be taken into account to explain such discrepancies [9,20,22,28]. …”
Section: Discussionmentioning
confidence: 99%
“…The aim of this multicenter observational study, carried out in the framework of the Dermatoepidemiology and Evidence-Based Dermatology Study Group of the Italian Association of Hospital Dermatologists, was to study a fairly large sample of Italian vitiligo patients by using the Dermatology Life Quality Index (DLQI) questionnaire, which has been successfully employed for the same purpose on subjects with vitiligo in other countries [7,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. The DLQI questionnaire is designed for use in adults (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [11] also observed that the quality of life correlates with patient's disease severity, but not with the doctor's disease severity assessment. As Kostopoulou et al [12] were studying the factors determining the psychological effects of vitiligo, they found that the disease severity perceived by the patients and the personalities of the patients were the determinants of quality of life. Augustin et al [13] developed a scale called Patient Benefit Index (PBI) to determine the expectations of vitiligo patients from the treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The scores range from 0 to 30 (0-1: no effect on patient's life, 2-5: small effect, 6-10: moderate effect, 11-20: very large effect, 21-30: extremely large effect). The score in most studies represents a moderate impact of vitiligo on quality of life (6-10) (Dolatshahi et al, 2008, Kostopoulou et al, 2009, Mechri et al, 2006, Ongenae et al, 2005a, Radtke et al, 2009. The highest mean DLQI value was observed in the patient group aged 20-29 years (Radtke et al, 2009).…”
Section: Quality Of Lifementioning
confidence: 99%
“…The highest mean DLQI value was observed in the patient group aged 20-29 years (Radtke et al, 2009). Perceived severity and patient's personality were predictors of quality of life impairment (Kostopoulou et al, 2009). There were statistically significant relationships between DLQI scores and marital status, skin phototype, and disease progression, respectively (Al Robaee, 2007, Dolatshahi et al, 2008, Ongenae et al, 2005a.…”
Section: Quality Of Lifementioning
confidence: 99%